Judokas Show Increased Resilience to Unpredictable Stance Perturbations. Issue 3 (June 2022) - Betelli, Marina T.; de Oliveira, Julia Á.; Coelho, Daniel B.; Teixeira, Luis A.
Combat sports are characterized by frequent large-scale stance perturbations that may lead to falls. In the present investigation, we compared compensatory arm and leg movements in response to unpredictable stance perturbations between judokas and other athletes whose sports present reduced balance demand, relative to combat sports. Specifically, we tested judokas ( n = 9), and a group of swimmers and runners ( n = 11, controls) in sudden support base displacements in the mediolateral direction, generated by a movable electronic platform, in the following modes: (a) rotation, (b) translation, and (c) combined rotation-translation. The platform was displaced to either side, in three peak velocities (cm/second or o /second) of 20 (low), 30 (moderate), or 40 (high), resulting in 18 distinct perturbations. We evaluated postural responses with a scale for analyzing the stability of compensatory arm and leg movements (CALM). Results showed that, in the most challenging perturbations, judokas had higher stability scores (arm, leg, and global) than did the comparison group. Higher scores for judokas reflected their increased rate of motionless arm and leg responses and absence of near-falls, compared to 30% falls in the most challenging perturbations for the swimmers and runners. As a practical application, judo training may help achieve stable compensatory limb movements in a way that parallels the benefits obtained from perturbation-based balance training in laboratory settings.